The future of foreign language education in the United States - Osborn, Terry A., 1966- (Contemporary language education., 2002)
Annotation Focuses on the possibilities for reform in foreign language education, including interdisciplinary, literary, teacher education, heritage language learning, and critical pedagogical approaches. Attention is also paid to epistemological, historical, and "new science" paradigmatic examinations of the field.